Upregulation of Systemic Inflammatory Pathways Following Anterior Cruciate Ligament Injury Relates to Both Cartilage and Muscular Changes: A Pilot Study. Issue 2 (25th September 2019) - Hunt, Emily R.; Villasanta‐Tezanos, Alejandro G.; Butterfield, Timothy A.; Lattermann, Christian; Jacobs, Cale A.
ABSTRACT: In conjunction with cartilage breakdown, muscle maladaptation including atrophy and increased fibrosis have been observed in the quadriceps following anterior cruciate ligament (ACL) injury. Previously observed upregulated muscle‐related proteins in the synovial fluid following ACL rupture allude to cellular communication between the joint and muscle. Therefore, the purpose of this study was to determine whether muscle‐related analytes are differentially expressed in the serum. Sixteen patients with an acute ACL tear participated in this IRB‐approved study. Serum was obtained at two different time points at a mean of 6 and 14 days post‐injury, and serum was analyzed by a highly multiplexed assay of 1, 300 proteins. Pathway analysis using DAVID was performed; genes included met three criteria: significant change between the two study time points using a paired t test, significant change between the two study time points using a Mann–Whitney non‐parametric test, and significant Benjamini post hoc analysis. Twelve analytes significantly increased between time points. Proteins chitinase‐3‐like protein 1 ( p = 0.01), insulin‐like growth factor binding protein 1 ( p = 0.01), insulin‐like growth factor binding protein 5 ( p = 0.02), renin ( p = 0.004), and lymphotoxin alpha 1: beta 2 ( p = 0.03) were significantly upregulated in serum following acute ACL injury. The current results confirm the inflammatory pattern previously seen in the synovial fluid thought to play a role in the progression of post‐traumatic osteoarthritis after ACL injury, and this data also provides further insights into important communication between the joint and quadriceps group, whose function is important in long term health. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 38:387‐392, 2020